Distribution and diversity of Fagaceae in Hidalgo, Mexico - Susana Valencia-A.; Gabriel Flores-Franco; Jaime Jiménez-Ramírez; Mauricio Mora-Jarvio (Botan‪ical Sciences, 2017)
Background: The family Fagaceae is one of the most important in temperate regions of the Northern hemisphere. Fagus and Quercus are distributed in Mexico, the former in Northeastern Mexico, while the latter reaches a high diversity in the Sierra Madre Oriental, Mexico. In Hidalgo state, located mainly in the Sierra Madre Oriental, knowledge of the Fagaceae diversity is still uncertain.